The Difference in Average of Maternal Serum Hypoxia-Inducible Factors-1α Levels between Early Onset and Late-Onset Severe Preeclampsia - David Perdana; Defrin Defrin; Firdawati Firdawati (Universitas Andalas, 2021)
The purpose of this study is to know the difference average of maternal serum levels of HIF-1α between early-onset and late-onset severe preeclampsia. This study used a cross sectional comparative study design that conducted in Februari 2020 - Agustus 2020 in the SMF / Obstetrics and Gynecology department of RSUP dr. M. Djamil Padang, RSUD Achmad Mochtar, RSUD Pariaman, RSUD M Zein Painan. We used consecutive sampling method which consists of 60 pregnant women who fulfill the inclusion and exclusion criteria. They were divided into two groups early-onset severe preeclampsia and late-onset severe preeclampsia. HIF-1α tests were done using ELISA method. The average of maternal serum levels of HIF-1α in late-onset severe preeclampsia is found to be the highest when compared to the early-onset severe preeclampsia, 1,37 ± 1,08 ng/ml vs 0,69 ± 0,11 ng/ml. This difference is significant with the Mann-whitney non parametrical statistical test (p <0.05). There is a significant difference average of maternal serum levels of HIF-1α between early-onset and late-onset severe preeclampsiaKeywords: early onset severe preeclampsia, late onset preeclampsia late onset, maternal serum levels of HIF-1α